The Legal Mechanisms for the Consumption of Urban Property in Algerian City - The Case of the City of Ouargla (Architecture Image Studies, 2025)
This study aims to understand the mechanisms of urban land loss in Algerian city. This is done by defining these mechanisms, explaining their rationale, identifying the stakeholders involved and their roles, and highlighting the impacts and consequences of their operation. Finally, it offers some solutions and recommendations that may lead to a review of their operating procedures or help curb their consumption of urban land. Through our study, we concluded that there is sometimes a lack of relationship and, at other times, a lack of coordination between the work of these mechanisms and urban planning schemes. This has led to the depletion of urban land and affected the city's urban expansion.